2016
DOI: 10.1186/s41256-016-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Health system strengthening and hypertension management in China

Abstract: BackgroundNon-communicable diseases are the leading causes of global burden of diseases, and hypertension is one of the most important risk factors. Hypertension prevalence doubled in China in the past decade and affects more than 300 million Chinese people. In the review we systematically searched peer-reviewed publications that link health system level factors with hypertension management in China and provide the current knowledge on how to improve a country’s health system to manage the hypertension epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This quality gap may be the result of weakness in the service delivery system; the split between preventive care and primary care provision systems may hinder the continuity and coordination of prevention, treatment, and effective control of hypertension. 21,29,30 Unlike hypertensive care patients in most developed countries, those in China are still receiving care from different providers: clinical care is provided by primary care physicians, preventive care and management by public health physicians, community-based intervention by community health workers, and patient education in both primary care facilities and the community. 31,32 Efforts in health system strengthening should be focused on bringing the different services together; offering hypertensive patients accessible, continuous, and coordinated care; and improving the quality of hypertension management in China.…”
Section: Discussionmentioning
confidence: 99%
“…This quality gap may be the result of weakness in the service delivery system; the split between preventive care and primary care provision systems may hinder the continuity and coordination of prevention, treatment, and effective control of hypertension. 21,29,30 Unlike hypertensive care patients in most developed countries, those in China are still receiving care from different providers: clinical care is provided by primary care physicians, preventive care and management by public health physicians, community-based intervention by community health workers, and patient education in both primary care facilities and the community. 31,32 Efforts in health system strengthening should be focused on bringing the different services together; offering hypertensive patients accessible, continuous, and coordinated care; and improving the quality of hypertension management in China.…”
Section: Discussionmentioning
confidence: 99%
“…China has the opportunities to mimic the success seen in the United States, given the country's health infrastructure, particularly in primary care. Free screening and routine management of hypertension have been provided since China's 2009 health reform 24, 25. Efforts are needed to scale up screening and use of antihypertensive medications as a part of expanding and improving primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension in China has been rising rapidly during the past two decades [14,15]. Pooled data from 178 studies between 1999 and 2014 revealed that the overall prevalence was 28.9% [16].…”
Section: Discussionmentioning
confidence: 99%